THE NURSE AS MAIN HEALTH ADVISOR OF PREGNANT WOMEN WITH THE HIV VIRUS - Lucas Viana Roly, Damião; Rodrigues da Silva, Natália; Gomes da Silva, Simone; Allyson Gomes Ferreira, Jefferson; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia; Lima Nogueira, Pollyana; Corrêa Bezerra de Araújo, Renata; Michele de Araujo Pedro, Fabiana; Rocha Nunes, Iasmin; Rocha Pereira, Vitória; Moraes Dolandeli Marques, Tatiane; et al. (Health and Society, 2022)
The time of pregnancy is generally expected that women with high expectations, but not always the same feel prepared for this period, generating some doubts and fear. When faced in a positive way, it is special, but for that to happen, it is necessary that this woman, to want to get pregnant, go through a pre-conception consultation, accompanied by a skilled health Identify adopted guidance strategies the nurse to pregnant women with HIV to reduce the risk of vertical transmission; analyze the influences of guidance provided to that pregnant women during prenatal, postpartum. We opted for the realization of an integrative review, was held search in the Virtual Health Library (VHL) in August 2015, using the keywords: Vertical transmission of infectious disease, HIV and Nursing associated with the Boolean AND operator. Results: Analyzing the articles appeared two themes: Nursing guidelines for reducing the risk of vertical transmission: the importance of nurses to reduce vertical transmission of HIV in Brazil is important, no doubt this professional develops activities relevant to public health from the instances of the grievances of the reduction policy to instances of comprehensive care to pregnant women, new mothers and mothers. Nursing orientation consequences of postpartum: health professionals, including nurses is critical to support families living with or affected by HIV. Conclusion: This research aims at the importance of professional training for nurses working in the area, as a skilled and sensitive nurse makes the advice of active listening process, generating trust between you and the woman, during consultations, one must realize a return that offered guidelines are being absorbed and practiced the same.